2016
DOI: 10.1007/s00484-016-1160-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated dynamics of bud dormancy and growth in temperate fruit trees relating to bud phenology adaptation, the case of apple and almond trees

Abstract: Few studies have focused on the characterization of bud dormancy and growth dynamics for temperate fruit species in temperate and mild cropping areas, although this is an appropriate framework to anticipate phenology adaptation facing future warming contexts which would potentially combine chill declines and heat increases. To examine this issue, two experimental approaches and field observations were used for high- and low-chill apple cultivars in temperate climate of southern France and in mild climates of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 37 publications
3
26
1
Order By: Relevance
“…Similar results were found by Benmoussa et al [23]. Furthermore, El Yaacoubi et al [15] found that low-chill apple cultivars showed very early flowering dates compared to high-chill cultivars. However, as mean bloom dates did not differ much between the 12 apple cultivars analyzed herein, no clear relationship could be found between the CR or the length of the chill/forcing phase and their bloom dates like those we found for almond.…”
Section: Chilling and Forcing Phases Delineation Using A Partial Leassupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results were found by Benmoussa et al [23]. Furthermore, El Yaacoubi et al [15] found that low-chill apple cultivars showed very early flowering dates compared to high-chill cultivars. However, as mean bloom dates did not differ much between the 12 apple cultivars analyzed herein, no clear relationship could be found between the CR or the length of the chill/forcing phase and their bloom dates like those we found for almond.…”
Section: Chilling and Forcing Phases Delineation Using A Partial Leassupporting
confidence: 79%
“…Furthermore, warming during the chilling phase could impede the cultivation of some species in their present locations if their CR are not met anymore [2]. In the case of temperate fruit trees, because of their need to fulfil CR to ensure homogeneous flowering and fruit set [3], the intensification of global warming may compromise the ability of many growers to satisfactorily produce the same array of crops as in the past [13][14][15]. On the other hand, such increases in temperature will allow the cultivation of species, such as citrus, that until now have been restricted because of too-low temperatures during winter.…”
Section: Introductionmentioning
confidence: 99%
“…Dormancy, when divided into three phases (para-, endo-, and ecodormancy), has the endodormancy as crucial one, because the cold accumulation during autumn/winter period is fundamental for the plant physiological processes during this phase. However, the use of sprouting inductors can serve as a supplement (El Yaacoubi et al 2016). In this research, it can be observed that it is very important to choose the correct bud inductor and its concentration, because not all inductors and not all tested concentrations could complement the lack of coldness and consequently induce a good sprouting.…”
Section: Resultsmentioning
confidence: 97%
“…Endodormancy completion is needed for the xylem vessel differentiation that allows for the rehydration of the developing bud [20]. Vegetative buds released from endodormancy could be in a dominant state and quickly grow during ecodormancy under high temperatures [21]. This could inhibit the growth of other buds by correlative inhibitions and lead to very short ecodormancy [7].…”
Section: Discussionmentioning
confidence: 99%
“…This could inhibit the growth of other buds by correlative inhibitions and lead to very short ecodormancy [7]. Additionally, it is possible that low chilling requirements cultivars such as Desmayo Largueta could better tolerate high temperatures during ecodormancy [21].…”
Section: Discussionmentioning
confidence: 99%